2015
DOI: 10.1007/s12311-015-0678-4
|View full text |Cite
|
Sign up to set email alerts
|

Case Study: Somatic Sprouts and Halo-Like Amorphous Materials of the Purkinje Cells in Huntington’s Disease

Abstract: We described a 63-year-old Japanese female with genetically confirmed Huntington's disease who showed unusual pathological findings in the cerebellum. This case exhibited typical neuropathological features as Huntington's disease, including severe degeneration of the neostriatum and widespread occurrence of ubiquitin and expanded polyglutamine-positive neuronal intranuclear and intracytoplasmic inclusions. The cerebellum was macroscopically unremarkable; however, somatic sprouts and halo-like amorphous materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Instead, localized changes and altered connectivity are more commonly reported than volume loss. For instance, Purkinje cell loss/degeneration is accompanied by somatic sprouts, halo-like amorphous materials, torpedoes, and granular cytoplasmic inclusions in Purkinje cells [73]. These changes localize to the oculomotor vermis (which would explain symptoms of impaired smooth eye pursuits, impaired Hoffman reflex, and hypotonia) [18].…”
Section: Cerebellar Dysfunction In Neurodegenerationmentioning
confidence: 99%
“…Instead, localized changes and altered connectivity are more commonly reported than volume loss. For instance, Purkinje cell loss/degeneration is accompanied by somatic sprouts, halo-like amorphous materials, torpedoes, and granular cytoplasmic inclusions in Purkinje cells [73]. These changes localize to the oculomotor vermis (which would explain symptoms of impaired smooth eye pursuits, impaired Hoffman reflex, and hypotonia) [18].…”
Section: Cerebellar Dysfunction In Neurodegenerationmentioning
confidence: 99%
“…8,9 In addition, we previously demonstrated that Huntington's disease is one of the diseases showing somatic sprouting of Purkinje cells. 7 Direct damages to Purkinje cells could be proposed in these diseases, such as abnormal protein accumulation; however, no apparent α-synuclein accumulation has been described in Purkinje cells of MSA. A synucleinopathy with specific glioneuronal degeneration, which is associated with early myelin dysfunction and neuronal degeneration related to retrograde axonal disease, is suggested as a central role in the disease process in MSA.…”
Section: Discussionmentioning
confidence: 63%
“…Details of the pathomechanism behind developing somatic sprouts are still uncertain. Several degenerative disorders have been reported to be associated with somatic sprouts of Purkinje cells, [2][3][4][5][6][7] including hereditary spinocerebellar ataxia. [3][4][5] In patients with SCA31, a large number of Purkinje cells with the somatic sprouting and halo-like structures were observed.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations